PRELIMINARY GEOID MODEL IN SAN JUAN PROVINCE: A CASE STUDY IN THE ANDES - TOCHO, CLAUDIA; MIRANDA, SILVIA; PACINO, MARIA CRISTINA; FORSBERG, RENE (Boletim de Ciências Geodésicas, 2008)
A high-resolution and high-precision detailed gravimetric geoid has been computed for San Juan province in Argentina, ranging from 27º S to 34º S in latitude and 72º'W to 65º W in longitude. The gravimetric geoid was calculated using the RTM method, a multiband spherical Stokes Fast Fourier Transformation, and the remove-restore technique for the spherical harmonic reference field and the terrain. As an external evaluation, the gravimetric quasigeoid/geoid was compared to the geoid heights obtained from 90 GPS/levelling points available for the province. Finally, a GPS-tailored local geoid, which fits the GPS observations, was computed. Keywords: Gravimetric Geoid; RTM Method; High Precision Geoid.